IMPLEMENTASI AUGMENTED REALITY (AR) PADA MEDIA INFORMASI KAWASAN WISATA TAMAN NASIONAL GUNUNG HALIMUN SALAK ENDAH - nanda suryana fadli (Jurnal Data Mining dan Sistem Informasi, 2023)
Tourist area information media is a medium needed by tourists to find information about tourist areas so they can travel and enjoy nature. Information media for the tourist area of Gunung Halimun Salak Endah National Park consists of a camping ground, queen crater, hot springs, and 7 waterfalls, and as for the price of the main entrance ticket, the price of the entrance ticket per tourist spot, the distance from the entrance gate to the tourist spot, existing facilities in tourist areas. Media information on tourist areas can be searched directly and indirectly. However, these sources of information are less interesting and less interactive. Therefore AR (Augmented reality) technology is the right solution to overcome this problem. This study aims to create an application using AR (Augmented reality) implementation technology on information media in the tourist area of Mount Halimun Salak Endah National Park based on Android. By utilizing the camera feature on smartphone devices to detect markers, 3D objects will appear. Augmented reality is the incorporation of an object that exists in the virtual world (virtual) into the real world in 2D or 3D form that can be seen and heard in real time. The method used in this research is Marker Based Tracking. Applications that utilize augmented reality technology in tourist areas can be used by tourists and the general public. Based on the results of the alpha and beta tests, it is known that the value is 5.67% for accuracy, relevance and completeness. It can be concluded that information media in tourist areas is appropriate to be used to assist information media for tourists, and people who want to visit the tourist area of Mount Halimun Salak Endah National Park, because it can increase interest and interest. This application will run on the Android 7.0 (Nougat) mobile platform and supports ARCore with an application capacity of 145MB.